Ingested Plastic in the Great Northern Diver, the Common Loon (Gavia immer) - Hilling, Thomas P.; Reynolds, Hannah T.; Breslin, Vincent T.; Pokras, Mark A. (Northeastern Naturalist, 2025)
Plastic pollution and its impact on water-reliant avifauna is a global, pervasive issue. We evaluated necropsy data of Gavia immer (Common Loon) from freshwater and marine environments in the northeastern US from 2011 to 2022, and found 16.2% (106/654) had ingested plastic items (macroplastics). We examined Common Loons stranded from 2020 to 2022, quantified macroscopic plastic items in detail, and processed the ingesta for suspected microplastics. We found macroplastics in 20.7% (11/53) and suspected microplastic particles, predominately clear fibers, in 100% (37/37) of the Common Loons. While we found no evidence that sex, mass, or geography correlated with microplastic load, both macroplastics and suspected microplastics were widespread and prevalent in Common Loon ingesta in the northeastern US. © 2025 Humboldt Field Research Institute. All rights reserved.
Keywords: dept.egm

Assessing the risk of contaminated sediments during small dam removal projects in the Long Island Sound watershed - Alix, Katelyn; Fedorchuk, Nicholas; Breslin, Vincent; Hoehne, Gary; Hayton, Jam; Balbachan, Kayla (Abstracts with programs - Geological Society of America, 2025)
Keywords: Computer science; Contamination; Ecology; Environmental science; Geology; Geotechnical engineering; Hydrology (agriculture); Oceanography; Sound (geography); Watershed; dept.egm; dept.esc

Metals, Organic Compounds, and Nutrients in Long Island Sound: Sources, Magnitudes, Trends, and Impacts - Varekamp, Johan C.; McElroy, Anne E.; Mullaney, John R.; Breslin, Vincent T. (Long Island Sound: Prospects for the Urban Sea, 2014)
Long Island Sound (LIS) is a relatively shallow estuary with a mean depth of 20 m (maximum depth 49 m) and a unique hydrology and history of pollutant loading. These factors have contributed to a wide variety of contamination problems in its muddy sediments, aquatic life, and water column. The LIS sediments are contaminated with toxic compounds and elements related to past and present wastewater discharges and runoff. These include nonpoint and stormwater runoff and groundwater discharges, whose character has changed over the years along with the evolution of its watershed and industrial history. Major impacts have resulted from the copious amounts of nutrients discharged into LIS through atmospheric deposition, domestic and industrial waste water flows, fertilizer releases, and urban runoff. All these sources and their effects are in essence the result of human presence and activities in the watershed, and the severity of pollutant loading and their impacts generally scales with total population in the watersheds surrounding LIS. Environmental legislation passed since the mid-to-late 1900s (e.g., Clean Air Act, Clean Water Act) has had a beneficial effect, however, and contaminant loadings for many toxic organic and inorganic chemicals and nutrients have diminished over the last few decades (O’Shea and Brosnan 2000; Trench et al. 2012; O’Connor and Lauenstein 2006; USEPA 2007). Major strides have been made in reducing the inflow of nutrients into LIS, but cultural eutrophication is still an ongoing problem and nutrient control efforts will need to continue. Nonetheless, LIS is still a heavily human impacted estuary (an “Urban Estuary,” as described for San Francisco Bay by Conomos 1979), and severe changes in water quality and sediment toxicity as well as ecosystem shifts have occurred since the European colonization in the early 1600s (Koppelman et al., 1976). The Sound has seen the most severe environmental changes over the last 400 years during its 10,000 year history (Lewis, this volume), suggesting that human impacts have overwhelmed the natural forces at play.
Citation Key Alias: lens.org/113-875-687-538-455
Keywords: Boston Harbor; Coastal Embayment; Marine Organic Matter; Striped Bass; White Perch; dept.egm